PI3K regulates MEK/ERK signaling in breast cancer via the Rac-GEF, P-Rex1 - Ebi, Hiromichi; Costa, Carlotta; Faber, Anthony C; Nishtala, Madhuri; Kotani, Hiroshi; Juric, Dejan; Della Pelle, Patricia; Song, Youngchul; Yano, Seiji; Mino-Kenudson, Mari; Benes, Cyril H; Engelman, Jeffrey A (Proceedings of the National Academy of Sciences - PNAS, 2013)
The PI3K pathway is genetically altered in excess of 70% of breast cancers, largely through PIK3CA mutation and HER2 amplification. Preclinical studies have suggested that these subsets of breast cancers are particularly sensitive to PI3K inhibitors; however, the reasons for this heightened sensitivity are mainly unknown. We investigated the signaling effects of PI3K inhibition in PIK3CA mutant and HER2 amplified breast cancers using PI3K inhibitors currently in clinical trials. Unexpectedly, we found that in PIK3CA mutant and HER2 amplified breast cancers sensitive to PI3K inhibitors, PI3K inhibition led to a rapid suppression of Rac1/p21-activated kinase (PAK)/protein kinase C-RAF (C-RAF)/ protein kinase MEK (MEK)/ERK signaling that did not involve RAS. Furthermore, PI3K inhibition led to an ERK-dependent up-regulation of the proapoptotic protein, BIM, followed by induction of apoptosis. Expression of a constitutively active form of Rac1 in these breast cancer models blocked PI3Ki-induced down-regulation of ERK phosphorylation, apoptosis, and mitigated PI3K inhibitor sensitivity in vivo. In contrast, protein kinase AKT inhibitors failed to block MEK/ERK signaling, did not up-regulate BIM, and failed to induce apoptosis. Finally, we identified phosphatidylinositol 3,4,5-trisphosphate-dependent Rac exchanger 1 (P-Rex1) as the PI(3,4,5)P3-dependent guanine exchange factor for Rac1 responsible for regulation of the Rac1/C-RAF/MEK/ERK pathway in these cells. The expression level of P-Rex1 correlates with sensitivity to PI3K inhibitors in these breast cancer cell lines. Thus, PI3K inhibitors have enhanced activity in PIK3CA mutant and HER2 amplified breast cancers in which PI3K inhibition down-regulates both the AKT and Rac1/ERK pathways. In addition, P-Rex1 may serve as a biomarker to predict response to single-agent PI3K inhibitors within this subset of breast cancers.